From microbial gene essentiality to novel antimicrobial drug targets - Mobegi, Fredrick; van Hijum, S.A.F.T.; Burghout, P.; Bootsma, H.J.; de Vries, S.P.W.; van der Gaast-de Jongh, C.E.; Simonetti, E.; Langereis, J.D.; Hermans, P.W.M.; de Jonge, M.I.; Zomer, A. (BMC, 2014)
Background: Bacterial respiratory tract infections, mainly caused by Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis are among the leading causes of global mortality and morbidity. Increased resistance of these pathogens to existing antibiotics necessitates the search for novel targets to develop potent antimicrobials.